Self-perceptions of decision making competence in Spanish football players - Luis Miguel Ruiz Pérez; Miriam Palomo Nieto; Virginia García Coll; José Antonio Navia Manzano; Javier Miñano Espín; Rudolf Psotta (Palacký University Olomouc, 2014)
Background: It is known that competence to make decisions is a fundamental aspect of sport competition. Objective:This study has analyzed the decision profile of a sample of Spanish football players of different levels of expertise. Methods: 690 Spanish football players of national and international level completed the decision making questionnaire, which cover three dimensions - perceived decision competence, decision anxiety and commitment with decision learning. MANCOVA and ANOVA analysis were carried out to analyse the differences in each dimension based on the level of expertise. Results: Results showed that perception of decision making competence increased and the anxiety decreased with the level of expertise. Conclusions: This study confirmed the usefulness of this questionnaire in the process of training for coaches and sport psychologists.